Reduction Mammaplasty: What Cup Size Will I Be?. Issue 6 (14th June 2019) - Chan, Marion; Lonie, Sarah; Mackay, Sean; MacGill, Kirstie
Abstract : Background: Predicting cup size after reduction mammaplasty is a challenge well recognized by plastic surgeons. This study presents a method whereby the weight of tissue to be excised can be predicted on the basis of the initial and desired cup size. Methods: Breast density was calculated from resection specimens. Cup volumes of a specific range of bra style were then measured by filling the bra cups with modeling clay on a mannequin and the volume measured via water displacement. These data were then correlated to breast tissue volume and weight. Results: The average breast tissue density calculated was 0.98 g/ml (SD = 0.05). Bra cup volume measurements showed a steady progression according to both cup and band sizes. A table was constructed to predict the weight of tissue required for excision to achieve the desired change in cup size. Conclusion: These results can assist plastic surgeons in predicting the amount of breast tissue to excise to achieve a given cup size. A secondary use of these results is a breast volume guide for implant planning.